The Influence of Liquidity, Profitability, Leverage and Company Size on Dividend Policy with Growth Opportunities as Moderating Variables in Manufacturing Companies Listed on the IDX - Haidil Putra; Rizki Sri Lasmini (Universitas Negeri Padang, 2023)
This study aims to analyze the effect of liquidity, profitability, leverage, and firm size on dividend policy with growth opportunities as a moderating variable. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. While the sample in this study was determined by purposive sampling method in order to obtain a total sample of 22 companies with a total of 110 data. The analytical method used is multiple linear regression analysis with data testing using IBM SPSS statistics 25. The results of this study indicate that (1) Liquidity has no significant effect on dividend policy, (2) Profitability has a negative and significant effect on dividend policy, (3) Leverage has a positive and significant effect on dividend policy, (4) Company size has a positive and significant effect on dividend policy, (5) Growth Opportunities cannot moderate the relationship between liquidity and dividend policy, and (6) Growth Opportunities can strengthen the relationship between profitability and dividend policy